Pengaruh Inflasi dan Investasi Terhadap Pengangguran di Provinsi Bali Tahun 1994 - 2013 - Prayuda, Mahanatha Giri; Urmila Dewi, Made Henny (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 1, Januari 2016 (pp. 1 - 215), 2016)
The problem of unemployment is a problem that will never run out for discussion. Unemployed or jobless is a term for people who do not work at all, are looking for work, working less than two days during the week or someone who is trying to get the job .Uemployed generally caused due to the work force or job seekers are not proportional to the number jobs are there that are able absord. This research was conducted aimed to examine the effect of inflation and investment against unemployment in the province of Bali in 1994-2013. The data used is secondary data. The analysis technique used in this study is a multipleregression. The result is inflation partial significant positive effect on unemployment. Means that the high inflation, unemployment increased. Investment in partial significant negative effect on unemployment. Means that the higher investment, rising unemployment and inflation and Investment simultaneous effect on unemployment. Means the higher inflation, investment will decrease and unemployment will decrease. The result are excepeted to provide input to the government in order to maintain the stability of inflation and invesment that the unemployment rate decrease.
Keywords: Inflation; Invesment; Unemployment